"Hybrid Orders" between Terrorism and Organized Crime: The Case of Al Qaeda in the Islamic Maghreb. Issue 2 (2nd April 2016) - Rosato, Valeria
ABSTRACT: This article analyzes the "nexus" between terrorism and organized crime in the Sahel. The arguments animating recent debates can be grouped into two distinct positions: the apocalyptic approach, which tends to exaggerate the threat of terrorism and its links with organized crime, and the conspiratorial approach, which reveals how the specter of terrorism comes to be manipulated by a range of actors for their own particular interests. This study offers an alternative view: thus far the region has not been subject to the spread and consolidation of Islamist ideology but rather to hybrid orders that are a complex dynamic of instrumental adaptation on the part of Islamist terrorists, criminal organizations, and the local population.